Wound Healing and Antioxidant Properties of Launaea procumbens Supported by Metabolomic Profiling and Molecular Docking - Shaimaa R. Ahmed; Ehab M. Mostafa; Arafa Musa; Enas Ezzat Rateb; Mohammad M. Al-Sanea; Dalia H. Abu-Baih; Mahmoud A. Elrehany; Entesar Ali Saber; Mostafa E. Rateb; Usama Ramadan Abdelmohsen (MDPI AG, 2022)
Wounds adversely affect people's quality of life and have psychological, social, and economic impacts. Herbal remedies of Launaea procumbens (LP) are used to treat wounds. In an excision wound model, topical application of LP significantly promoted wound closure (on day 14, LP-treated animals had the highest percentages of wound closure in comparison with the other groups, as the wound was entirely closed with a closure percentage of 100%, p < 0.05). Histological analysis revealed a considerable rise in the number of fibroblasts, the amount of collagen, and its cross-linking in LP-treated wounds. Gene expression patterns showed significant elevation of TGF-β levels (2.1-fold change after 7 days treatment and 2.7-fold change in 14 days treatment) and downregulation of the inflammatory TNF-α and IL-1β levels in LP-treated wounds. Regarding in vitro antioxidant activity, LP extract significantly diminished the formation of H2O2 radical (IC50 = 171.6 μg/mL) and scavenged the superoxide radical (IC50 of 286.7 µg/mL), indicating antioxidant potential in a dose-dependent manner. Dereplication of the secondary metabolites using LC-HRMS resulted in the annotation of 16 metabolites. The identified compounds were docked against important wound-healing targets, including vascular endothelial growth factor (VEGF), collagen α-1, tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and transforming growth factor-β (TGF-β). Among dereplicated compounds, luteolin 8-C-glucoside (orientin) demonstrated binding potential to four investigated targets (VEGF, interleukin 1β, TNF-α, and collagen α-1). To conclude, Launaea procumbens extract could be regarded as a promising topical therapy to promote wound healing in excisional wounds, and luteolin 8-C-glucoside (orientin), one of its constituents, is a potential wound-healing drug lead.